PENGARUH JARAK TANAM DAN DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS (Zea mays Var. saccharata Sturt) KULTIVAR BONANZA F1. - Sucipto Adikarna; Amran Jaenudin; Dwi Purnomo (Program Studi Ilmu Pertanian Pascasarjana UGJ, 2022)
The research aims to determine; (1) the effect of the combination of spacing and dose of NPK fertilizer on the growth and yield of sweet corn, and (2) the combination of spacing and dose of NPK fertilizer that gave the best effect on the growth and yield of sweet corn of Bonanza F1 cultivar. The research was carried out for 3 (months) months, starting from September to December 2021. The method used in this study is an experimental method, using a randomized block design, 9 combination treatments of spacing and doses of NPK fertilizer and repeated three times. To determine the effect of the treatment being tested, analysis of variance was used through the F test, with further testing using the Scott Knott test at a significance level of 5 percent. The results showed: (1) Plant spacing and NPK fertilizer had a significant effect on plant height, number of leaves per plant, stem diameter, diameter of cob without stalks, length of cobs without kelobot, weight of cob without kelobot per plant and per plot, and (2) A distance of 75 cm x 50 cm and a spacing of 75 cm x 60 cm combined with the application of 300 kg/ha of NPK fertilizer gave the highest weights of cobs without husks per plot, namely 3.67 kg and 3.54 kg or equivalent to 12.23 tons/ha. ha and 11.80 tons/ha.